Ferroresonant processes in 10 kV power grids and there control - Yatseyko, Andriy; Hyrska, Kateryna (Lviv Polytechnic Publishing House, 2015)
The problem of ferroresonance processes in power gris with isolated neutral was reviewed. Conditions of the existence of such phenomena and basic principles of theis control were establihed. A new approaches of protection for 10 kV electric systems from ferroresonant processes were given. The research was conducted using digital simulation and reasons for offered protection methods were defined.
Keywords: electric systems; power grids; ferroresonant processes; digital model; isolated neutral; voltage transformers